Erysiphe symphoricarpi (Erysiphales), the first record in Ukraine - Heluta, V.P.; Siahaan, S.A.S.; Takamatsu, S. (Український ботанічний журнал, 2016)
A powdery mildew on an ornamental plant Symphoricarpos albus (Caprifoliaceae) was found in Kyiv (Ukraine)
in October 2015. The causal agent was mainly in the anamorphic state, but the teleomorph in the form of several fruiting
bodies (chasmothecia) were present. Only one of these was almost mature. Its morphology suggested it belonged to
the common North American species Erysiphe (Microsphaera) symphoricarpi. Two separate phylogenetic analyses using
ITS and 28S rDNA sequences showed that the fungus on S. albus collected in Ukraine grouped with E. symphoricarpi
collected in Hungary, UK, and USA with strong bootstrap supports (MP = 100%, ML = 100%). This is the first record
of this species in Ukraine. It is assumed that the disease will not have a significant impact on green spaces, because the
pathogen develops in late autumn and fruiting bodies are rare. Повідомляється, що в 2015 р. в Україні була зареєстрована борошниста роса на декоративній рослині
Symphoricarpos albus (Caprifoliaceae). Гриб-збудник хвороби формував переважно конідіальну стадію, однак було
знайдено і декілька плодових тіл, лише одне з них було
майже зрілим. Його морфологічні ознаки свідчать, що
знайдений гриб належить до північно-американського
Erysiphe (Microsphaera) symphoricarpi. Був також здійснений
філогенетичний аналіз із залученням ITS та 28S рДНКпослідовностей. У результаті показано, що зразок з
України з великою достовірністю об'єднується в одну
групу з трьома зразками E. symphoricarpi, зібраними у
Великій Британії, Угорщині та США. Це перша знахідка даного гриба в Україні. Він виявлений в Києві, лише
в одному локалітеті. Допускається, що гриб не буде
завдавати значної шкоди зеленим насадженням України, оскільки він розвивається пізно восени і майже не
утворює плодових тіл. Сообщается, что в 2015 г. в Украине была зарегистрирована мучнистая роса на декоративном растении
Symphoricarpos albus (Caprifoliaceae). Гриб-возбудитель заболевания развивался преимущественно на анаморфной
стадии, однако было найдено и несколько плодовых тел.
Только одно из них было почти зрелым. Его морфологические признаки свидетельствуют о том, что найденный
гриб принадлежит к северно-американскому Erysiphe
(Microsphaera) symphoricarpi. Был также проведен
филогенетический анализ с использованием ITS и 28S
рДНК-последовательностей. В результате показано, что
образец из Украины с большой достоверностью объединяется в одну группу с тремя образцами E. symphoricarpi,
собранными в Великобритании, Венгрии и США. Это
первая находка данного гриба в Украине. Он обнаружен
в Киеве, только в одном локалитете. Предполагается, что
гриб не будет приносить значительного вреда зеленым
насаждениям Украины, поскольку развивается поздней
осенью и практически не образует плодовых тел.